Utilization of Less Valuable Species of Timbers of India - Rehman, M. A. (Indian Forester, 1959)
Out of a large number of species of woods growing in this country only about half a dozen timbers, as the primary species, have till recently been commercially exploited and extensively used. About 30 or 40 species which fall in the category of less valuable species are also in use due to their suitability for specific uses. These timbers are briefly discussed in the paper. A list of less valuable timbers which can be put to major uses after seasoning only, or after seasoning and presentative treatment, is also given.